Resveratrol promotes chondrogenesis of human Wharton's jelly stem cells in a hyperglycemic state by modulating the expression of inflammation-related cytokines. Issue 1 (1st January 2020) - Sultan, Samar; Alalmie, Ali; Noorwali, Abdulwahab; Alyamani, Aisha; Shaabad, Manal; Alfakeeh, Saadiah; Bahmaid, Afnan; Ahmed, Farid; Pushparaj, Peter; Kalamegam, Gauthaman
ABSTRACT: A high glucose (HG) or state predispose to osteoarthritis and has adverse effects on cartilage regeneration. Human Wharton's jelly stem cells (hWJSCs) isolated from umbilical cords have been reported to promote cartilage regeneration. Furthermore, resveratrol (RSV) has numerous beneficial effects including anti-inflammatory properties. Therefore, we investigated the effects of HG (28 mM), RSV (17 µM), and both (HG-RSV) on chondrogenesis of hWJSCs as assessed by proteoglycan deposition, proliferation, and pro-inflammatory cytokine production compared with the control (5 mM glucose). Toluidine blue staining of proteoglycans was positive under all conditions. HG enhanced the growth of differentiated cells (DCs) on days 14 and 21. Growth of DCs were decreased on day 4, but increased on days 14 and 21, following treatment with RSV and HG-RSV. Compared with the HG group, HG-RSV decreased the proliferation of DCs on days 4 and 14. COLI, COLII, and COLX transcripts were increased, while SOX9 transcript was decreased in all treated groups. IL-1α, IL-6 and IL-8 levels were decreased in RSV and HG-RSV groups. The levels of G-CSF and GM-CSF were high in HG-RSV group, while HG reduced the GM-CSF level. Thus, under HG conditions, RSV promotes chondrogenesis by increasing proteoglycans and collagen synthesis as well as by regulating the pro-inflammatory cytokines.